Evaluating CRC-8 Detection Performance in Cloud Traffic - J., Vijitha Ananthi; S., Jahnavi; M., Sushmitha; M., Vasantha; S., Bhanu Sasank (IRO Journal on Sustainable Wireless Systems, 2026)
The cloud infrastructure settings used to maintain security across distributed servers, lively and reliable data transport is necessary. Error detection techniques like Cyclic Redundancy Check (CRC) provides accuracy with low cost is important for increasing traffic volumes. This paper examines the binary format and functional role of the CRC-8 polynomial to keep data validity during server-to-server communication. The CRC identify the most common error patterns by this analysis. If it fails in some situations then sudden errors will match the generating polynomial. The performance of CRC has the detection accuracy, correction capability, bandwidth cost and relevance across various networking environments proposed in this paper compared to Forward Error Correction and Two-Dimensional Parity Checking. CRC receives 50,000 messages daily. A 1 KB payload with 16-bit CRC capability is included in every transfer. According to the test, CRC produces a 0.195% delay per message and needs 0.095MB of bandwidth. Furthermore, CRC prevents 2% of retransmissions by saving ten times more bandwidth. These result show that the polynomial provides high error detection with less resource usage is one of the most effective techniques for high-volume cloud traffic. However, FEC or hybrid algorithms are the most suitable for settings that require strong correction capabilities such as satellite connections, radio channels, or latency-sensitive systems.